PENINGKATAN KEMAMPUAN ANALISIS KLAUSA MATA KULIAH SINTAKSIS DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT - Prihatin, Yulianah (Discovery, 2017)
One of the problems that arise in the course of learning the syntax is generally done with college pulpit so that the learning is centered on the lecturer. This causes saturation for students and not the appearance of the activity within the student. Therefore it is necessary to have appropriate learning models in the course of Syntax, one with a model of the type of cooperative learning TGT. This study focused on the process of learning using TGT type of cooperative learning model, barriers to learning, student achievement during the learning and teaching model of cooperative-type linkage TGT with increased ability of students in the analysis of the clause. This study aims to determine the learning process, barriers to learning, student achievement during the learning and teaching model of cooperative-type linkage TGT with increased ability of students in the analysis of the clause. Keywords : clause, TGT